2022
DOI: 10.1016/j.ijpam.2021.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, clinical features, and outcomes of coronavirus disease among children in Al-Madinah, Saudi Arabia

Abstract: Background and Objective: Coronavirus disease (COVID-19) is milder with favorable outcomes in children than in adults. However, detailed data regarding COVID-19 in children from Saudi Arabia are scarce. This study aimed to describe COVID-19 among children in Al-Madinah, Saudi Arabia. Methods: This retrospective observational study included children <14 years old hospitalized with COVID-19 between May 1, 2020 and July 31, 2020. Clinical data, COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…According to our study results, respiratory distress syndrome prevalence rates in Saudi Arabia ranged between 5.1% in Jeddah and highest 84% in Al-Madinah [11,12]. Saudi Arabia had a comparable prevalence of respiratory distress syndrome in several studies, 56%, 60%, 20% [13][14][15] also 8% of the cases admitted to the PICU unit.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…According to our study results, respiratory distress syndrome prevalence rates in Saudi Arabia ranged between 5.1% in Jeddah and highest 84% in Al-Madinah [11,12]. Saudi Arabia had a comparable prevalence of respiratory distress syndrome in several studies, 56%, 60%, 20% [13][14][15] also 8% of the cases admitted to the PICU unit.…”
Section: Resultssupporting
confidence: 50%
“…(2020) [12] Al-Madinah Twenty-nine (27%) of the 106 patients had at least one pre-existing ailment, with bronchial asthma being the most prevalent (9.4%). In terms of COVID-19 disease severity, the majority of cases (84%), including one patient (0.94%), satisfied the MIS-C criteria.…”
Section: Alshengeti Et Almentioning
confidence: 99%
“…Indeed, the laboratory findings showed that among hospitalized patients, lymphocytopenia and leukopenia, in addition to elevated levels of ferritin, D-dimer, and C-reactive proteins, were encountered (Almoosa et al, 2020;Alnajjar et al, 2021;Mosalli et al, 2021;Shahin et al, 2021). The mortality rate was very low in the infected children of this country, with this latter not exceeding four deaths among all reports (Almoosa et al, 2020;Alnajjar et al, 2021;Alshengeti et al, 2021;Asseri et al, 2021;Hijazi et al, 2021;Kari et al, 2021b;Mosalli et al, 2021;AlGhamdi et al, 2022). Interestingly, in one study, it was found that 21% of hospitalized children infected with SARS-CoV-2 developed acute kidney injury.…”
Section: Childrenmentioning
confidence: 91%
“…A substantial portion were asymptomatic ( Ahmad et al, 2021 ; Almuzaini et al, 2021 ; Hijazi et al, 2021 ) with this rate ranging from 27.9% ( Mosalli et al, 2021 ) to 54.6% ( Alharbi et al, 2021 ). Among symptomatic ones, the most common reported symptoms were fever, cough, runny nose, and shortness of breath ( Harbi et al, 2020 ; Ahmad et al, 2021 ; Alharbi et al, 2021 ; Alshengeti et al, 2021 ; Mosalli et al, 2021 ; Shahin et al, 2021 ; AlGhamdi et al, 2022 ). Gastrointestinal symptoms were also described but to a lesser extent ( Almoosa et al, 2020 ; Alharbi et al, 2021 ; Almuzaini et al, 2021 ; Alnajjar et al, 2021 ; Shahin et al, 2021 ).…”
Section: Childrenmentioning
confidence: 99%
See 1 more Smart Citation